2006
DOI: 10.1124/dmd.105.007559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P-Glycoprotein on Intestinal Absorption and Brain Penetration of Antiallergic Agent Bepotastine Besilate

Abstract: ABSTRACT:The antiallergic agent bepotastine besilate is a nonsedating, second-generation H1-antagonist with high oral absorption and negligible distribution into brain. To clarify the role of P-glycoprotein (P-gp) in the pharmacokinetics of bepotastine, intestinal absorption and brain penetration studies were performed. In conclusion, bepotastine is a substrate for P-gp, and P-gp clearly limited the brain distribution of bepotastine, whereas the effect of P-gp on intestinal absorption of bepotastine was minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…In addition, a significant stimulatory effect was exhibited by verapamil over 0.25 to 100 M with a K m and V max of 5.98 Ϯ 0.7 M and 89.34 Ϯ 2.84 nmol/min/mg protein, respectively. The estimated K m value for verapamil to PgP/MDR1-mediated ATP hydrolysis was in agreement with previously reported values (4.06 -6.10 M) (Adachi et al, 2001;Ohashi et al, 2006).…”
Section: Transport Of Glabridin In Control Mdckii and Mdr1-md-ckii Mosupporting
confidence: 81%
“…In addition, a significant stimulatory effect was exhibited by verapamil over 0.25 to 100 M with a K m and V max of 5.98 Ϯ 0.7 M and 89.34 Ϯ 2.84 nmol/min/mg protein, respectively. The estimated K m value for verapamil to PgP/MDR1-mediated ATP hydrolysis was in agreement with previously reported values (4.06 -6.10 M) (Adachi et al, 2001;Ohashi et al, 2006).…”
Section: Transport Of Glabridin In Control Mdckii and Mdr1-md-ckii Mosupporting
confidence: 81%
“…Ohashi et al showed that bepotastine and fexofenadine were substrates for P-gp with similar corrected efflux ratio values in an in vitro study, although the permeability of bepotastine was high compared with that of fexofenadine. They demonstrated that the high absorption of bepotastine was derived from the high permeability in the proximal region of the small intestine, whereas the permeability of fexofenadine was low both in the proximal and distal region of the small intestine [24]. This study also supports our speculation for the discrimination of the MDR1 effect on the absorption of P-gp substrates.…”
Section: Discussionsupporting
confidence: 66%
“…Rifampicin has been shown to decrease the rate of absorption of cyclosporine [27]. Further, in the presence of P-glycoprotein (P-gp) inhibitors, the k a of [ 14 C]bepotastine in the small intestine has been shown to increase [28]. Nevirapine may be a substrate for P-gp [29,30].…”
Section: Discussionmentioning
confidence: 99%